Conditioned Media of Human Umbilical Cord Blood Mesenchymal Stem Cell-derived Secretome Induced Apoptosis and Inhibited Growth of HeLa Cells - Ferry Sandra; Janti Sudiono; Elina Ardiani Sidharta; Elisabeth Pricilia Sunata; Dea Jane Sungkono; Yanni Dirgantara; Angliana Chouw (The Indonesian Biomedical Journal, 2014)
BACKGROUND: Secreted factors contained in conditioned media (CM) of human umbilical cord blood mesenchymal stem cells (hUCB-MSCs) known as secretome, was suspected to have important roles in regulating cells. This study was conducted to investigate the role of CM-hUCB-MSCs-derived secretome in apoptosis and growth of HeLa cells.METHODS: HeLa cells were treated with secretome in various concentrations (0, 0.2, 2 and 20%) for 24 and 48 hours. Trypan blue exclusion assay was performed to detect cell viability. Meanwhile sub-G1 apoptotic assay was performed to detect apoptotic cells. The transition of mitochondrial transmembrane potential (TMP), which occurs in the apoptotic process, was analyzed by mitochondrial membrane potential (ΔΨM) assay. Both sub-G1 and ΔΨM assays were performed using FACSCanto flow cytometer. Statistical analyses were conducted using IBM SPSS Statistics to detect significance level at p<0.05.RESULTS: Secretome significantly induced cell death starting at concentration of 0.2% within a 24-hour period (p<0.05). Secretome significantly induced cell death in concentration and time dependent manner (p<0.05). The cell death was then confirmed as apoptosis through sub-G1 analysis. Due to the underlying apoptotic mechanism, we found distinct decrease of TMP, indicating an increase in mitochondrial membrane permeability of HeLa cells. In addition, we found that HeLa cell growth was inhibited partially by secretome.CONCLUSION: Taken together, we conclude that CMhUCB-MSCs-derived secretome significantly induced apoptosis of HeLa cells in a concentration and time dependent manner through mitochondrial apoptotic pathway. The secretome might also play important role in inhibiting HeLa cell growth.KEYWORDS: umbilical cord blood, mesenchymal stem cell, secretome, apoptosis, growth, cancer